A Rare Case of Multiple Myeloma Identified Following the Diagnosis of Amyloidosis of the Tongue - Hideka Kanemoto; Kyoichi Obata; Koichi Kadoya; Kisho Ono; Hotaka Kawai; Yuki Kunisada; Mayumi Yao; Soichiro Ibaragi (Case Reports in Dentistry)
Amyloidosis is a disease in which amyloid protein is deposited in organs and tissues, resulting in functional impairment. Amyloidosis occurs in 12%–30% of patients with multiple myeloma, but in rare cases, amyloidosis may precede the diagnosis of multiple myeloma. Our patient was a 76-year-old Japanese male on dialysis. Multiple nodules accompanied by ulcers were observed on his tongue. He had no subjective symptoms or clinical findings associated with multiple myeloma. The histopathological findings suggested amyloidosis. We suspected both systemic and localized amyloidosis and performed a comprehensive systemic examination. Since the patient had been on dialysis for only a short period of time (~3 months), dialysis-related amyloidosis was ruled out. After blood and urine tests, a diagnosis of multiple myeloma was made. Chemotherapy treatment was started, but the patient’s multiple myeloma could not be suppressed and the tongue amyloidosis worsened, leading to his death 2 years and 2 months after the initial diagnosis.